Factors Influencing Teachers’ Job Satisfaction in Kathmandu Valley - Thapaliya, Adit (Nepalese Journal of Economics, 2025)
This study examines the factors influencing teachers’ job satisfaction in Kathmandu Valley. Teachers’ job satisfaction is the dependent variable. The selected independent variables are salary, bonus, working environment, recognition, job security and workload. The primary source of data is used to assess the opinion of respondents regarding salary, bonus, working environment, recognition, job security, workload and teachers’ job satisfaction. The study is based on 145 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the factors influencing teachers’ job satisfaction in Kathmandu Valley. The study showed a positive impact of salary on teachers’ job satisfaction. It indicates that competitive salary enhances the teachers’ job satisfaction. Similarly, the study showed a positive impact of bonus on teachers’ job satisfaction. It indicates that performance-based bonus systems motivate employees to excel, boosting productivity, job satisfaction, and loyalty to the company. Likewise, the study showed a positive impact of working environment on teachers’ job satisfaction. It indicates that employees who thrive in a positive working environment are more likely to perform better and stay motivated. Further, the study showed a positive impact of recognition on teachers’ job satisfaction. It indicates that greater recognition attracts individuals to remain motivated and engaged in their roles. In addition, the study showed a positive impact of job security on teachers’ job satisfaction. It indicates that job security encourages teachers to feel more satisfied and stable in their roles. Moreover, the study showed a positive impact of workload on teachers’ job satisfaction. It indicates that a manageable workload encourages teachers to feel more satisfied and engaged in their roles.